Keanekaragaman Jenis Tumbuhan Famili Agavaceae Di Pekarangan Fakultas Sains Dan Teknologi Uin Sunan Gunung Djati Bandung - Rahmawati, Alfiah; Khoerunnisa, Aida Syakira; Supriyatna, Ateng (Cangkok, 2023)
This study aims to explore the diversity of plant species of the Agavaceae family in the yard of the Faculty of Science and Technology UIN Sunan Gunung Djati Bandung. The research was conducted using the method of observation, recommendations, descriptions, and calculations of plant diversity in the Agavaceae family. The data obtained were analyzed using scientific literature as a reference. The results showed that the Agavaceae family had a moderate bearing. Mother-in-law's tongue (Sansevieria trifasciata) was the most common species with 37 individuals, followed by Cyclops (Agave attenuata) with 13 individuals. Yellow Mother-in-law's Tongue (Sansevieria trifasciata laurentii), Sword-in-Law's Tongue (Sansevieria cylindrica), and Song of India (Dracaena reflexa) were also found in smaller quantities. These plants of the Agavaceae family have a beautiful and unique aesthetic value, and some of them have health benefits and the ability to absorb pollutants.